Molecular-level swelling behaviors of poly (ethylene terephthalate) glycolysis using ionic liquids as catalyst. (5th March 2023) - Zheng, Weizhong; Liu, Chenyi; Wei, Xin; Sun, Weizhen; Zhao, Ling
Highlights: Catalytic performance of ionic liquids for PET glycolysis was studied. [Cho][OAc] shows the highest yield of BHET with 66.7 % at 180 ℃. Interface property for PET glycolysis with [Cho][OAc] was studied by MD simulation. [Cho][OAc] can enhance the PET swelling in EG. Abstract: Ionic liquids (ILs) are considered as the high-efficiency catalysts for PET glycolysis. However, insight into the swelling behaviors for PET glycolysis with IL still remains seldom. Hence, temperature-dependent interfacial properties and catalytic performance for PET glycolysis with [Cho][OAc] catalysts were investigated using molecular dynamic (MD) simulation and experiments. MD results indicate that [Cho][OAc] can enhance the PET swelling in ethylene glycol (EG), especially at high temperature, contributing to the enhanced conversion of PET. Strong interaction between EG and [OAc] - as well as PET and [Cho] + can intensify the access of reaction sites between PET and EG, important to the high-efficiency PET glycolysis. Furthermore, experimental results confirm that the PET conversion catalyzed by [Cho][OAc] increases with elevated temperature with almost 100 % PET conversion and 66.7 % BHET yield at 180 ℃, which strongly supports MD results. The information provides an essential understanding about the swelling for PET glycolysis with IL catalysts.